Pengaruh Pengaruh Bonus Demografi Dan Industrialisasi Terhadap Pengangguran Terdidik Usia Muda Di Indonesia Tahun 2018-2022 - Putri, Fadhila Ramadhani Gita; Suhartini, Atik Mar'atis (Politeknik Statistika STIS, 2024)
Indonesia became the second highest youth unemployment in ASEAN countries. The rate of young educated unemployment in Indonesia continues to fluctuate during the period 2018-2022. The large supply of labor during the demographic dividen period must be utilized optimally in order to bring benefits such as economic growth and reduce unemployment. This study aims to analyze the rate of young educated unemployment in Indonesia from 2018-2022 using panel data regression. The results show that the population dependency ratio, industrial sector GRDP, agricultural sector GRDP and average worker wages affect young educated unemployment. The government is expected to increase the labor-intensive industrial sector and promote modern agriculture to young workers in order to reduce unemployment among young educated people.